Periodisasi Pemerintahan Banu Abbasiyah (Kajian Sejarah Politik) - Nur Fadhillah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, The Banu Abbasids were the second Caliphate in power in Baghdad for more than five centuries (132H / 750 AD to 656H / 1258 AD) after conquering the Banu Umayyah Caliphate. During the five centuries of rule the Banu Abbasid caliphate reached its heyday in the field of science, both general and religious knowledge. The pattern of government adopted by Banu Abbasiyah is divided into five periods based on political, social and cultural changes. In the first and third periods of the Banu Abbasid government the Persian culture was strongly influenced and in this period it emphasized the fostering of Islamic civilization and culture rather than the expansion of territory. In the second and fourth periods influenced by Turkish culture which is very dominant in politics and government. Whereas the fifth period was marked by the entry of the Seljuks into Baghdad until the fall of Baghdad to the Mongols. Keywords: Periodization, Government, Banu Abbasiyah